Novel variable-section tumble air intake system - LI HUIJUN; DING SHUYONG; YOU YI (2017)
The invention discloses a novel variable-section tumble air intake system. According to the system, by changing the air intake section of each air intake manifold under the low-load working condition, the air intake flow speed is increased, the air intake tumble ratio is increased in cooperation with an air inlet partition, the wall wetting phenomenon of a cylinder liner, the piston top face and a valve due to fuel oil injection in a cylinder is lowered, carbon deposition is reduced, the emission is lowered, the oil dilution rate is lowered, the uniformity of mixed gas is improved, and the fuel economy is increased. At a high load, by adjusting the air intake section, the air intake resistance is lowered, the sufficient air inflow is provided for a generator, and the requirement of a whole vehicle for the large power of an engine is guaranteed. 本发明公开了款新型可变截面及滚流进气系统，该系统通过改变低负荷工况下的进气歧管进气截面，从而提高进气流速，配合进气道隔板提高了进气滚流比，降低缸内喷射燃油对缸套、活塞顶面及气门的湿壁现象，减少积碳，降低排放，降低机油稀释率，提高混合气均匀性、燃油经济性。在高负荷时，通过调整进气截面，降低了进气阻力，为发电机提供了足够进气量，保证整车